Pathogenic fungi (Sordariomycetes) associated with annual and perennial crops in Northern Thailand - Maryam Fallahi; Alireza Armand; Fatimah Al-Otibi; Kevin D. Hyde; Ruvishika S. Jayawardena (MycoKeys)
Phytopathogenic fungi induce severe diseases in plant hosts, potentially leading to significant crop quantity and quality reductions. In this study, we isolated and identified pathogenic fungi that threaten the successful cultivation of annual and perennial crops in northern Thailand. Samples with leaf spots, fruit rot, wilting, and dieback symptoms were collected from 19 different crops in Chiang Rai, Chiang Mai, and Sakon Nakhon provinces in Thailand. Out of 183 isolates, 27 were selected for molecular analysis and multi-gene phylogenetic study based on their diverse host range, geographical distribution, and an initial morphological assessment. Four of the most species-diverse fungal genera – Colletotrichum, Diaporthe, Fusarium, and Neopestalotiopsis – were identified, along with 23 taxa, including four novel species. Six species of Colletotrichum (Colletotrichum abelmoschi sp. nov., C. fructicola, C. makassarense, C. plurivorum, C. siamense, and C. spaethianum), six species of Diaporthe (Diaporthe fistulosi sp. nov., D. hongkongensis, D. melongenicola sp. nov., D. rosae, D. sennicola, and D. siamensis), five species of Fusarium (Fusarium bubalinum, F. languescens, F. nirenbergiae, F. sulawesiense, and F. tanahbumbuense), and three species of Neopestalotiopsis (Neopestalotiopsis formicidarum, N. theobromicola sp. nov., and N. zakeelii, along with three unspecified taxa), were isolated and characterized in this study. Additionally, fourteen new host records and eight new geographical records are reported. Pathogenicity tests were carried out for selected strains, and the results confirmed their pathogenicity on their host plants. This study offers new insights into the diversity of species of plant pathogenic fungi in northern Thailand.